Real Time Web Enabled Hostel Booking System - Pamela Kiden Simon (Uganda Christian University, 2025)
The increased off-campus housing had result due to UCU-BBUC's growing student body. There was a yearly competition for available housing because there aren't enough off-campus hostels to satisfy the demand. The inefficiency of the outdated methods that hostel managers and administrators were still employing to run their establishments had a detrimental effect on the effective administration of the facilities. The goal of this project was to create and design a web-enabled hostel booking management system that will expedite administrative and management activities as well as registration and booking procedures. The system will be created with HTML, JavaScript, and CSS for the front end, MySQL database for data storage, and JavaScript programming language for the back end. The system will eliminate the issues of the old techniques; it will be graphic-user interface oriented, secure, efficient and reliable.